Pemanfaatan Ekstrak Daun Ketapang (Terminalia Catappa L) Sebagai Green Inhibitor Dengan Metode Maserasi Untuk Mengendalikan Laju Korosi Pada Aluminium - Roin Nuretha; Komalasari Komalasari; Sri Rezeki Muria (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2021)
Terminalia catappa L leaf extract has a considerable influence in decreasing the corrosion rate of a metal, because it contains tannin compounds which can be used as corrosion inhibitors. The purpose of this study was to determine the effect of addition of Terminalia catappa L leaf extract inhibitors on the corrosion rate of aluminum with variations in immersion time and determine the inhibition efficiency of variations in the concentration of Terminalia catappa L leaf extract on aluminum in corrosive media. The parameters varied in this study were the immersion time of the maceration process, the inhibitor concentration added in the corrosive solution of sodium chloride, namely 0, 1,5 and 2 g/L as well as variations in the time of corrosion testing at 36, 48, 60 and 72 hours. The time of maceration process shows that the longer the contact time, the greater the concentration of crude tannin, while the time of immersion of aluminum shows the longer the immersion time, the corrosion rate tends to decrease with the addition of inhibitors and the higher the value of inhibitory efficiency. The best crude tannin concentration was obtained during the maceration process for 6 days with a crude tannin concentration of 84,90 mg / L. The lowest corrosion rate was obtained when the addition of 2 g / L inhibitor in the corrosive NaCl medium with immersion time of 72 hours was 0,347 mm / year. The results showed that the best inhibition efficiency value using ketapang leaf extract inhibitor was added to the inhibitor 2 gr / L in 0,5 M corrosive media soaked for 72 hours with an efficiency value of 90,00%. Keywords: aluminum, corrosion rate, inhibitors, maceration, Terminalia catappa L leaf